Legal Certainty Over Ownership Certificates of Building Buildings of Apartment Units Based on Law No. 20 of 2011 Concerning Apartment Houses. 20 of 2011 on Flats - Ni Luh Wiwik Sariani; Erikson Sihotang; Komang Edy Dharma Saputra (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Legal certainty in property ownership is crucial for protecting the rights and interests of property owners. This study examines the legal certainty provided by ownership certificates for flats under Indonesia's "Law No. 20 of 2011" (UURS). It also explores the legal implications of constructing flats on land with building use rights, a status that differs from full ownership rights. Using a normative research method, the study analyzes relevant laws, regulations, and academic literature to understand how legal frameworks govern flat ownership and ensure the legitimacy of ownership certificates. The findings reveal that ownership certificates for flats confer private ownership of specific units and related common areas, but legal challenges arise when flats are constructed on land with building use rights, especially concerning the renewal of these rights. The study underscores the importance of continuous legal oversight and clear legislative guidelines to maintain and strengthen legal certainty over ownership certificates. Additionally, it highlights the potential legal risks and uncertainties that flat owners may face if the underlying land rights are not properly managed or renewed. The study concludes that while ownership certificates offer significant legal protection, the dependence on building use rights for the underlying land introduces potential vulnerabilities. Future research should explore the legal and practical implications of the expiration and renewal of building use rights, the impact on flat ownership, and alternative legal frameworks that could provide greater security for property owners.